Therapeutic effect of turmeric on radiodermatitis: A systematic review. Issue 5 (5th March 2023) - Ostadi, Atieh; Arab‐Zozani, Morteza; Zarei, Elham; Ferns, Gordon A.; Bahrami, Afsane
Abstract: Radiodermatitis (RD) occurs in 95% of cancer patients undergoing radiation therapy. At present, there is no effective treatment for the management of this complication of radiotherapy. Turmeric ( Curcuma longa ) is a polyphenolic and biologically active natural compound with various pharmacological functions. The aim of this systematic review was to determine the efficacy of curcumin supplementation for reducing RD severity. This review complied with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. A comprehensive literature search was conducted in Cochrane library, PubMed, Scopus, Web of Science, and MEDLINE databases. A total of seven studies comprising 473 cases and 552 controls were included in this review. Four studies demonstrated that curcumin supplementation had a beneficial effect on RD intensity. These data provide evidence for the potential clinical use of curcumin in supportive cancer care. Further large prospective and well‐designed trials are warranted to exactly determine the "real effective extract, supplemental form and dose of curcumin" for RD prevention and treatment of patients receiving radiotherapy. Abstract : Radiodermatitis (RD) occurs in 95% of cancer patients undergoing radiation therapy. At present, there is no effective treatment for the management of this complication of RD. Turmeric ( Curcuma longa ) is a polyphenolic and biologically active natural compound with various pharmacological functions. The aim of this systematic review and meta‐analysis was to determine the efficacy of curcumin supplementation at reducing RD severity. Most of the studies demonstrated that curcumin supplementation had a beneficial effect on RD intensity. These data provide strong evidence of curcumin's clinical value in supportive cancer care.